Management of Popo village development strategy as a marine tourism village in Takalar Regency - Machmury, Andri (Technium Sustainability, 2021)
The purpose of this research is to find out the right tourism development strategy to be implemented in Popo village as a coastal tourism village in Takalar Regency. The method of this research is descriptive research. The instruments in this study include; Observation of Data Documentation, Interview and Questionnaire. The result of the research shows that the development of tourist villages requires support from various parties so that they can become income for the community in the tourist village. In the development of tourist villages, there are various factors including driving factors and inhibiting factors. The driving factor of the tourist village being the driving force for the promotion of the tourist village will be a factor inhibiting the development of the tourist village so that it can be accepted and managed so that it can be entered as a tourism partner village.